Hype and Hope in Imagined Energy Futures. - KEEFER, CHRIS (Quadrant Magazine)
The article explores the promises and setbacks of energy technologies like nuclear power and photovoltaics. Topics discussed include the early optimism around breeder reactors, the rapid growth of solar energy, and the comparison between historical and contemporary visions of energy abundance.